The Relationship Between Nurse Behavior with the Compliance of the Use of Personal Protective Equipment (PPE) in the Inpatient Room of Efarina Hospital Pangkalan Kerinci - Nurmala; Rina Valensi; Novita Sinaga (PT Inovasi Pratama Internasional, 2022)
Occupational Safety and Health (K3) is an effort to create a safe, comfortable working atmosphere, and the ultimate goal is to achieve the highest possible productivity. Therefor K3 is absolutely necessary to be carried out in every type of work field without exception. K3 efforts are expected to prevent and reduce the risk of accidents and illnesses due to work (Hiperkes Bandung, 2008). The purpose of this study was to determine the relationship between nurse behavior and compliance. Use of Personal Protective Equipment (PPE) in the Inpatient Room of the Efarina Pangkalan Kerinci Hospital in 2021. The research design is observational through a cross-sectional approach. This type of research is quantitative and analytic in nature. The population is all nurses who work in the Inpatient Room of Efarina Hospital Pangkalan Kerinci as many as 52 people. The entire population (total sampling). Research results Based on Chi-square analysis (% ²), the relationship between knowledge and compliance with the use of PPE obtained results P-value = 0.024 Using a = 0.05 and p-value < 0.05, then Hp is rejected and H is accepted. Based on the relationship between attitude and compliance with the use of PPE, the Chi-Sguare analysis (%²) obtained a value of